AB0235 DENOSUMAB INCREASE THE BONE MINERAL DENSITY REGARDLESS OF DISEASE ACTIVITY, THE BIOLOGICAL DISEASE-MODIFYING ANTIRHEUMATIC DRUGS, THE CONCOMITANT TYPE OF VITAMIN D, AND PRETREATMENT OF OSTEOPOROSIS IN PATIENTS WITH RHEUMATOID ARTHRITIS. (13th June 2020) - Anno, S.; Okano, T.; Inui, K.; Koike, T.; Nakamura, H.
Abstract : Background: Osteoporosis is one of the major comorbidities in patients with rheumatoid arthritis (RA). There are a lot of evidence that denosumab increase bone mineral density (BMD) in patients with osteoporosis. However, there are few reports investigated the influence of denosumab in patients with RA. Objectives: We evaluated the BMD change in patients with RA treated denosumab and assessed the effect of various factors, such as disease activity, biological disease-modifying anti-rheumatic drugs (bDMARDs) use, concomitant medications of osteoporosis and pretreatment of osteoporosis. Methods: This study included 140 consecutive RA patients (135 female, mean age was 70.6 ± 8.6 years) who fullfilled the criteria of osteoporosis and treated with denosumab. BMD at the lumbar spine, proximal femoral and femoral neck were evaluated by dual energy X-ray absorptiometry at baseline and one year after treatment. We evaluated the influence of disease activity, bDMARDs use, the concomitant type of vitamin D and pretreatment of osteoporosis for BMD change. Results: BMD change at the lumbar spine, proximal femoral and femoral neck were 5.9% (p<0.01), 4.0% (p<0.01), and 1.2% (p=0.36) durling one year. There were no differences in improvement ratio of BMD between each parameters (fig 1 ). Disease activity: 75 patients in remission or low disease activity and 65 patients in moderate or high disease activity were 6.4 vs 5.3% (p=0.91), 3.0 vs 5.1% (p=0.73), 2.0 vs 0.3% (p=0.1). bDMARDs: 45 patients with bDMARDs (anti-tumor necrosis factor inhibitors (TNF): 23, tocilizmab (TCZ): 13, abatacept (ABT): 7, Tofacitinib: 2) and 93 patients without bDMARDs were 6.0 vs 5.8% (p=0.31), 4.3 vs 4.1% (p=0.57), -0.2 vs 1.8% (p=0.18). Type of vitamin D: 47 patients taking active form vitamin D and 60 patients taking native form vitamin D were 5.5 vs 6.8% (p=0.82), 3.1 vs 3.8% (p=0.93), 0.4 vs 1.9% (p=0.14). Pretreatment of osteoporosis: 74 patients with pretreatment of osteoporosis (bisphosphonate:58, teriparatide:16) and 66 patients without pretreatment of osteoporosis were 6.9 vs 5.4% (p=0.41), 0.9 vs 4.0% (p=0.22), 2.0 vs 1.2% (p=0.68). Moreover, BMD change were not different in bDMARDs type, 5.0, 6.4, 0.5% in TNF group, 4.8, 0.7, -1.9% in TCZ group, 9.7, 4.9, 0.2% in ABT group (TNF vs TCZ: p=0.83, 0.98, 0.81, TNF vs ABT: p=0.83, 0.41, 0.97, TCZ vs ABT: p=0.98, 0.43, 0.9). There were no difference between bisphosphonate and teriparatide (6.2 vs 6.9%: p=0.49, 4.8 vs 0.9%: p=0.35, 0.9 vs 2.0%: p=0.49). Conclusion: Denosumab improved BMD in patients with RA independently regardless of disease activity, bDMARDs, the concomitant type of vitamin D and pretreatment of osteoporosis. References: [1]Y Nakamura et al, Arch Osteoporos: 2017; 12:80. [2]K Kaneko et al, Journal of Experimental Orthopaedics: 2019; 6:41. [3]T Suzuki et al, Therapeutics and Clinical Risk Management: 2018; 14:453–459. Acknowledgments: We wish to thank Atsuko Kamiyama, Tomoko Nakatsuka, Masato Uematsu and all participants in this study. Disclosure of Interests: Shohei Anno: None declared, Tadashi Okano Grant/research support from: AbbVie, Eisai, Mitsubishi Tanabe Pharma Corporation and Nipponkayaku, Speakers bureau: AbbVie, Asahikasei, Astellas Pharma Inc, Ayumi Pharmaceutical, Bristol-Myers Squibb, Chugai Pharmaceutical, Daiich Sankyo, Eisai, Janssen, Lilly, Mitsubishi Tanabe Pharma Corporation, Novartis Pharma, Ono Pharmaceutical, Pfizer, Sanofi, Takeda Pharmaceutical, Teijin Pharma and UCB, Kentaro Inui Grant/research support from: Janssen Pharmaceutical K.K., Astellas Pharma Inc., Sanofi K.K., Abbvie GK, Takeda Pharmaceutical Co. Ltd., QOL RD Co. Ltd., Mitsubishi Tanabe Pharma, Ono Pharmaceutical Co. Ltd., Eisai Co., Ltd., , Speakers bureau: Daiichi Sankyo Co. Ltd., Mitsubishi Tanabe Pharma, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Takeda Pharmaceutical Co. Ltd., Ono Pharmaceutical Co. Ltd., Abbvie GK, Pfizer Inc., Eisai Co., Ltd., Chugai Pharmaceutical Co., Ltd., Tatsuya Koike Grant/research support from: AbbVie, Astellas Pharma Inc, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen, Lilly, Mitsubishi Tanabe Pharma Corporation, MSD, Ono Pharmaceutical, Pfizer, Roche, Takeda Pharmaceutical, Teijin Pharma, and UCB, Speakers bureau: AbbVie, Astellas Pharma Inc, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen, Lilly, Mitsubishi Tanabe Pharma Corporation, MSD, Ono Pharmaceutical, Pfizer, Roche, Takeda Pharmaceutical, Teijin Pharma, and UCB, Hiroaki Nakamura Grant/research support from: Astellas Pharma Inc. and Asahi Kasei Pharma Co.